Performance and Physicochemical Quality of Quail Eggs Given Bandotan (Ageratum conyzoides L.) Leaf Extract - Hariono Hariono; Ekayanti Mulyawati Kaiin; Tuti Suryati; Niken Ulupi; Rudi Afnan (Institut Pertanian Bogor, 2025)
The purpose of this study was to determine the influence of bandotan (Ageratum conyzoides L.) leaf extract on the production performance and physicochemical quality of quail eggs raised in tropical settings with ambient temperatures that exceed the comfort zone. A total of 200 female quails aged 6 weeks were reared in colony cages for 30 days. They were separated into four treatments with five replications, each with ten quails. Bandotan leaf extract was administered in dosages of 0%, 0.15%, 0.30%, and 0.45% per quail daily. The parameters measured included feed intake, feed conversion, egg production, egg mass, mortality, egg physical quality, and cholesterol and malondialdehyde (MDA) levels in egg yolks. Adding bandotan leaf extract to drinking water significantly improved quail production performance (p < 0.05). A dose of 0.30% resulted in the highest feed consumption, output, and egg mass, as well as significantly lower mortality rates, indicating its effectiveness in boosting the productivity and health of laying quails. Although it did not have a significant influence on the physical quality of eggs, administration of the extract at that dose significantly reduced MDA levels, egg cholesterol levels, and boosted antioxidant activity (p < 0.05). This demonstrates that bandotan leaf extract at a dose of 0.30% is beneficial in improving the production performance and chemical quality of heat-stressed quail eggs while preserving their physical quality. Keywords: bandotan, eggs, malondialdehyde, productive performance, quail